2021
DOI: 10.1177/13623613211003430
|View full text |Cite
|
Sign up to set email alerts
|

Short report: Patterns of US federal autism research funding during 2017–2019

Abstract: In 2017, the Interagency Autism Coordinating Committee, a federal advisory panel consisting of autism researchers and community members, recommended that funders of autism research prioritize research projects on: (1) treatments/interventions, (2) evidence-based services, and (3) lifespan issues. We sought to describe research funding since this recommendation was made. We searched the databases of the three largest federal funders of autism research in the United States (National Institutes of Health, Departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Our findings also provide the first description, to our knowledge, of characteristics of autism research articles with most downloads, citations, social media shares, and news coverage. Interestingly, despite being the largest area of funding for autism research, studies on the biology of autism were not among the most downloaded, cited, or shared articles (Harris et al, 2021 ). In contrast, most of the highly downloaded, cited and shared articles focused on high-priority research areas identified by the IACC like treatments and interventions and services (IACC, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also provide the first description, to our knowledge, of characteristics of autism research articles with most downloads, citations, social media shares, and news coverage. Interestingly, despite being the largest area of funding for autism research, studies on the biology of autism were not among the most downloaded, cited, or shared articles (Harris et al, 2021 ). In contrast, most of the highly downloaded, cited and shared articles focused on high-priority research areas identified by the IACC like treatments and interventions and services (IACC, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The International Classification of Functioning, Disability and Health, which is the World Health Organization's framework for measuring health and disability at both individual and population levels, is consistent with this broader perspective (Bölte et al, 2014). Yet, most of the published autism research, and the funding that supports it, remains focused on basic and clinical science (Cervantes et al, 2021; Harris et al, 2021).…”
Section: Figurementioning
confidence: 99%
“…Yet, few federal funding sources have explicitly supported systems‐wide research to identify mechanisms for improving access, service delivery, outcomes and wellbeing for these youth. In fact, the portion of combined federal and private funding supporting inquiry into lifespan services for autistic youth and young adults has repeatedly failed to move beyond 2% of all autism research funding (Interagency Autism Coordinating Committee (IACC), December, 2021), indicating the need for better alignment of research funding with national strategic goals aimed at meeting the needs of autistic adults (Cervantes et al, 2021; Harris et al, 2021).…”
Section: Introductionmentioning
confidence: 99%